The triphenylmethane dye brilliant blue G is only moderately effective at inhibiting amyloid formation by human amylin or at disaggregating amylin amyloid fibrils, but interferes with amyloid assays; Implications for inhibitor design. - Rehana Akter; Alexander Zhyvoloup; Bingqian Zheng; Surita R Bhatia; Daniel P Raleigh (PLoS ONE)
The development of inhibitors of islet amyloid formation is important as pancreatic amyloid deposition contributes to type-2 diabetes and islet transplant failure. The Alzheimer's Aβ peptide and human amylin (h-amylin), the polypeptide responsible for amyloid formation in type-2 diabetes, share common physio-chemical features and some inhibitors of Aβ also inhibit amyloid formation by h-amylin and vice versa. Thus, a popular and potentially useful strategy to find lead compounds for anti-amylin amyloid agents is to examine compounds that have effects on Aβ amyloid formation. The triphenylmethane dye, brilliant blue G (BBG, Sodium;3-[[4-[(E)-[4-(4-ethoxyanilino)phenyl]-[4-[ethyl-[(3-sulfonatophenyl)methyl]azaniumylidene]-2-methylcyclohexa-2,5-dien-1-ylidene]methyl]-N-ethyl-3-methylanilino]methyl]benzenesulfonate) has been shown to modulate Aβ amyloid formation and inhibit Aβ induced toxicity. However, the effects of BBG on h-amylin have not been examined, although other triphenylmethane derivatives inhibit h-amylin amyloid formation. The compound has only a modest impact on h-amylin amyloid formation unless it is added in significant excess. BBG also remodels preformed h-amylin amyloid fibrils if added in excess, however BBG has no significant effect on h-amylin induced toxicity towards cultured β-cells or cultured CHO-T cells except at high concentrations. BBG is shown to interfere with standard thioflavin-T assays of h-amylin amyloid formation and disaggregation, highlighting the difficulty of interpreting such experiments in the absence of other measurements. BBG also interferes with ANS based assays of h-amylin amyloid formation. The work highlights the differences between inhibition of Aβ and h-amylin amyloid formation, illustrates the limitation of using Aβ inhibitors as leads for h-amylin amyloid inhibitors, and reinforces the difficulties in interpreting dye binding assays of amyloid formation.